PENGARUH KESADARAN, SANKSI, DAN INSENTIF PAJAK TERHADAP KEPATUHAN WAJIB PAJAK BADAN PADA MASA PANDEMI COVID-19 - Nadinda, Ida Ayu Istri Anom; Budiartha, I Ketut (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.11.TAHUN.2023, 2023)
The Covid pandemic is hitting the country right now. This pandemic will result in reduced tax revenues, and a slowdown in national economic growth. This study aims to determine the effect of awareness, sanctions, and tax incentives on corporate taxpayer compliance. The population in this study are corporate taxpayers with a limited liability company (PT) which is recorded at 5,542 in the Badung Region. The number of samples in this study were 100 corporate taxpayers who were willing to fill out a questionnaire. The sampling technique used in this study was convenience sampling, which is a method of determining the sample by selecting samples freely at will, conducted randomly by considering the ease of access that can be reached by researchers. The data analysis technique used is multiple linear regression analysis and uses the SPSS program as an analytical tool. The results of this study indicate that tax awareness, tax sanctions, and tax incentives have a positive effect on taxpayer compliance. This research is expected to be used as a reference and consideration for the government to make policies that can improve taxpayer compliance so that it can help increase state revenue through tax payments by taxpayers